Light‐Activated Conjugated Polymers for Antibacterial Photodynamic and Photothermal Therapy. Issue 7 (20th May 2021) - Fedatto Abelha, Thais; Rodrigues Lima Caires, Anderson
Abstract : With the growing crisis of the availability of effective antimicrobial treatments, the use of phototherapy has gained increasing interest as an alternative to traditional antibiotic therapy. Even though phototherapy is already used in the clinic, there is an emerging interest in new materials with enhanced antimicrobial activity triggered by light. Among the different light‐responsive materials, conjugated polymers are emerging candidates with successful application in the field of antimicrobial photodynamic and photothermal therapy. Due to their organic composition, easy processability, tailorability of physicochemical properties, and capability of reactive oxygen species (ROS) and heat generation, their use as photoresponsive agents against bacteria has greatly expanded. Conjugated polymers have been designed to interact with specific bacterial targets, and their chemical composition has been optimized to enhance ROS and/or heat generation and new cationic polymers have been developed for augmented water solubility and increased interaction with negatively charged bacteria. Herein, the use of conjugated polymers in the field of phototherapy is discussed, focusing on the different approaches that have improved their performance against bacteria and their current preclinical safety assessment. Abstract : Conjugated polymers are versatile organic materials with useful optical properties that are applied to biomedicine. Their light absorption energy is transformed into ROS and/or heat, which inactivates bacteria through multitargeted mechanisms. Due to their easy processability, good biocompatibility, and amenable design for specific interaction with bacteria, conjugated polymers are promising photoresponsive antimicrobial agents.